Cooling-Heating Unit for Human Muscles - Gudaitis, R.; Tamulevičius, S. (Elektronika ir Elektrotechnika, 2005)
The unit is made on base of microprocessor and Peltier effect thermoelectric module. There is presented the principle of operation of unit. The unit is designed to work in continuous hot or cold, or cycle with predetermined time for cold and hot. In this paper the method of determining of heat flux into the muscle by law of Fourier is presented. The experiments had been performed on muscles of different size – gastrocnemius caput mediale, aductor pollicis, biceps femoris. The results are presented in graphic form. There are presented calculation of heat flux into the muscle. Ill.9, bibl. 5 (in Lithuanian; summaries in Lithuanian, English and Russian).